Centro de integración deportivo Río Frio (2023)
In the following paper the development of Rio Frio sports integration center located in Floridablanca, Santander is presented. Nowadays, the significance that the topic of sports action has obtained, lead us to question ourselves about the state and progress of the framework of the situations for the act of different sports activities, as long as this paper raises an architectural perspective of how is possible to address one of the issues that is presented with greater meticulousness in various urban communities in Colombia, in this case, in the Bucaramanga metropolitan area as well as the lack of sports infrastructure, which it is not unusual for the municipality of Floridablanca.